Exploratory Study of Rural Physicians' Self-Directed Learning Experiences in a Digital Age. Issue 4 (2016) - Curran, Vernon; Fleet, Lisa; Simmons, Karla; Ravalia, Mohamed; Snow, Pamela
Abstract : Introduction: The nature and characteristics of self-directed learning (SDL) by physicians has been transformed with the growth in digital, social, and mobile technologies (DSMTs). Although these technologies present opportunities for greater "just-in-time" information seeking, there are issues for ensuring effective and efficient usage to compliment one's repertoire for continuous learning. The purpose of this study was to explore the SDL experiences of rural physicians and the potential of DSMTs for supporting their continuing professional development (CPD). Methods: Semistructured interviews were conducted with a purposive sample of rural physicians. Interview data were transcribed verbatim and analyzed using NVivo analytical software and thematic analysis. Results: Fourteen ( N = 14) interviews were conducted and key thematic categories that emerged included key triggers, methods of undertaking SDL, barriers, and supports. Methods and resources for undertaking SDL have evolved considerably, and rural physicians report greater usage of mobile phones, tablets, and laptop computers for updating their knowledge and skills and in responding to patient questions/problems. Mobile technologies, and some social media, can serve as "triggers" in instigating SDL and a greater usage of DSMTs, particularly at "point of care, " may result in higher levels of SDL. Social media is met with some scrutiny and ambivalence, mainly because of the "credibility" of information and risks associated with digital professionalism. Discussion: DSMTs are growing in popularity as a key resource to support SDL for rural physicians. Mobile technologies are enabling greater "point-of-care" learning and more efficient information seeking. Effective use of DSMTs for SDL has implications for enhancing just-in-time learning and quality of care. Increasing use of DSMTs and their new effect on SDL raises the need for reflection on conceptualizations of the SDL process. The "digital age" has implications for our CPD credit systems and the roles of CPD providers in supporting SDL using DSMTs.